Z badań nad tekstem czytania porannego na czwartek Wielkiego Tygodnia w Ewangeliarzu Archangielskim 1092 roku - Szwed, Zofia (Studia Rossica Posnaniensia, 2016)
The article is an attempt to analyze the text of the morning reading for Holy Thursday in the 1092 Archangelsk Gospel referenced to the oldest Slavonic traditions of the Holy Bible translations. So far, researchers have focused on the morning reading for Holy Wednesday, which played an important role in the study of the complete edition of Aprakos Gospel. Less attention has been paid to the reading for Holy Thursday, a text which although textologically close to the reading for Holy Wednesday, is very different in the lexical dimension.